Determinants of Corporate Credit Growth - Jeger Situmorang; Jojok Dwiridotjahjono (Advances in Economics & Financial Studies, 2026)
Purpose: This study aims to analyze the effect of inflation, the BI 7-Day Reverse Repo Rate, Rupiah exchange rates, and gold prices on monthly outstanding loan distribution at PT Makmur Bersama Gadai Probolinggo Branch during the 2020–2025 period. Research Method: This study employed a quantitative associative approach using saturated sampling, with 72 monthly time-series observations. Secondary data were analyzed using multiple linear regression with the Cochrane-Orcutt transformation to address autocorrelation. Results and Discussion: The findings indicate that macroeconomic variables are significantly associated with the monthly distribution of outstanding loans. Partially, gold prices show a significant positive relationship, while the BI 7-Day Reverse Repo Rate demonstrates a significant negative relationship. Meanwhile, inflation and Rupiah exchange rates are not statistically significant. The model shows limited explanatory power, suggesting that the distribution of financing may also be influenced by other operational and customer-related factors not captured by the model. Implications: The findings provide practical insights for private pawn institutions on managing collateral valuation and financing strategies amid fluctuating macroeconomic conditions. Originality: This study focuses on a private pawn institution that implements a high Loan-to-Value (LTV) financing policy. This focus area has remained underexplored in previous studies, where state-owned pawn institutions have dominated.